Focused ion beam microfabrication of single-crystal nanobridge toward Fe(Te, Se)-based Josephson device. Issue 1 (July 2021) - Miyazawa, Takamaro; Tadokoro, Naoki; Horikawa, Shumpei; Tamegai, Tsuyoshi; Sun, Yue; Kitano, Haruhisa
Abstract: We report the fabrication and the transport measurements of FeTe1-x Sex ( x =0.4, 1) nanobridges along the c axis, toward the appearance of Josephson effects in single-crystal devices. Cross sectional areas of both FeTe0.6 Se0.4 and FeSe nanobridges were systematically reduced to 0.06 μm 2 by using a new method based on the focused ion beam (FIB) techniques. The critical current Ic measured by the current-voltage characteristics is roughly two orders of magnitude smaller than that for the conventional microbridges with larger cross sections, while the Ic Rn product, where R n is the normal-state resistance along the c axis, is still 3-4 times larger than the theoretical value for the appearance of Josephson effects. We argue the importance of the development of single-crystal Josephson devices and the comparison between FeTe0.6 Se0.4 and FeSe nanobridges.